Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ange.202104958
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dimensional Inorganic Tin Perovskite Solar Cells Prepared by Templated Growth

Abstract: The manipulation of the dimensionality and nanostructures based on the precise control of the crystal growth kinetics boosts the flourishing development of perovskite optoelectronic materials and devices. Herein, a low‐dimensional inorganic tin halide perovskite, CsSnBrI2−x(SCN)x, with a mixed 2D and 3D structure is fabricated. A kinetic study indicates that Sn(SCN)2 and phenylethylamine hydroiodate can form a 2D perovskite structure that acts as a template for the growth of the 3D perovskite CsSnBrI2−x(SCN)x.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Considering the high stability of RP perovskites, Ramirez et al introduced (BA) 2 (FA 0.85 Cs 0.15 ) n-1 (Pb 0.6 Sn 0.4 ) n I 3n+1 perovskites by inserting BA + into 3D FA/Cs perovskites to form 2D domains. [82] The mixed Sn-Pb hybrid perovskite system showed a low E g of 1.24 eV with the optimal n value of 5, where the resulted device showed 10.6% efficiency with improved stability. Therefore, partial substitution of the A site by large hydrophobic cation could reduce both oxygen and moisture ingress in mixed Sn-Pb perovskites.…”
Section: Ruddlesden-popper (Rp) Sn-based Perovskitesmentioning
confidence: 95%
“…Considering the high stability of RP perovskites, Ramirez et al introduced (BA) 2 (FA 0.85 Cs 0.15 ) n-1 (Pb 0.6 Sn 0.4 ) n I 3n+1 perovskites by inserting BA + into 3D FA/Cs perovskites to form 2D domains. [82] The mixed Sn-Pb hybrid perovskite system showed a low E g of 1.24 eV with the optimal n value of 5, where the resulted device showed 10.6% efficiency with improved stability. Therefore, partial substitution of the A site by large hydrophobic cation could reduce both oxygen and moisture ingress in mixed Sn-Pb perovskites.…”
Section: Ruddlesden-popper (Rp) Sn-based Perovskitesmentioning
confidence: 95%
“…The resulting film presents large grain size, superior out-of-plane orientation, and lower defect density, contributing to a champion PCE of 5.01% with much-enhanced thermal stability and oxidation resistance. 108 In addition, ethylammonium (EA) and allylammonium (ALA) cations have also been employed to construct 2D phases to regulate the crystal orientation of Sn-based PSCs. 109,110 These studies highlight the feasibility and effectiveness of forming lowdimensional phases for the growth of highly oriented 3D perovskites.…”
Section: Amine Saltsmentioning
confidence: 99%
“…The theoretical calculation revealed that the cleavage energy of the PEA 2 SnI 4− x SCN x phase is lower than that of PEA 2 SnI 4 and CsSnBrI 2 , so the intermediate template PEA 2 SnI 4− x SCN x was first grown, which is experimentally confirmed by the crystal growth kinetics tracking (Figure 11D,E). The resulting film presents large grain size, superior out‐of‐plane orientation, and lower defect density, contributing to a champion PCE of 5.01% with much‐enhanced thermal stability and oxidation resistance 108 . In addition, ethylammonium (EA) and allylammonium (ALA) cations have also been employed to construct 2D phases to regulate the crystal orientation of Sn‐based PSCs 109,110 .…”
Section: Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the introduction of low-dimensional structure materials can also significantly improve the stability and quality of Sn-based perovskites. 33 Also, previous reports have shown that the introduction of conventional organic cation halide salts (such as phenethylammonium ions, PEA + ) resulted in the formation of low-dimensional perovskites. [34][35][36] Meanwhile, PEA + can reduce the diffusion of O 2 and passivate the surface defects due to the large molecules of PEA + , PEAI (2-phenylethanamine iodide) as a passivating agent exhibits greater stability than MAI.…”
Section: Introductionmentioning
confidence: 99%